On the identity of two Mexican species of Ageratina (Eupatorieae, Asteraceae): A. grandifolia and A. rivalis - Oscar Hinojosa-Espinosa; José Luis Villaseñor; Enrique Ortiz (Botan‪ical Sciences, 2019)
Background: Ageratina, with 167 species, constitutes the most diverse genus of the Mexican Asteraceae and the sixth most diverse of the vascular plants in Mexico. The taxonomy of the genus is complex, due to its number of species and the numerous inadequately delimited taxa or with intricate and confusing nomenclature. In addition, little known species have sometimes remained under the synonymy of another different species, as in the case of A. rivalis, which has been considered as a synonym of A. grandifolia.